Zhongshan-ling yige xiandai zhengzhi fuhao de dansheng = Sun Yat-sen's mausoleum: The making of a political symbol in modern China - Li, Gongzhong (Dongfang-lishi-xueshu-wenku, 2009)
See summary in Chinese